2019
DOI: 10.1259/bjr.20190073
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative MRI features and clinical laboratory indicators for predicting the early therapeutic response of hepatocellular carcinoma to transcatheter arterial chemoembolization combined with High-intensity focused ultrasound treatment

Abstract: Objectives: To evaluate the value of preoperative MRI features and laboratory indicators in predicting the early response of hepatocellular carcinoma (HCC) to transcatheter arterial chemoembolization (TACE) combined with high-intensity focused ultrasound (HIFU) treatment and to establish a preoperative prediction model. Methods: A total of 188 patients with 223 tumors who underwent TACE/HIFU treatment from January 2011 to June 2017 were included. Tumors were divided into three groups (< 2 cm, 2 – 5 cm,> … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…We suggested that the TBIL was an independent risk factor for tumor response. However, several previous studies have demonstrated that the TBIL cannot be used as a clinical risk factor for the estimation of treatment efficacy but could predict survival in HCC patients treated with TACE ( 15 , 25 ). Further research should be conducted on the correlation between the TBIL and treatment efficacy of TACE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggested that the TBIL was an independent risk factor for tumor response. However, several previous studies have demonstrated that the TBIL cannot be used as a clinical risk factor for the estimation of treatment efficacy but could predict survival in HCC patients treated with TACE ( 15 , 25 ). Further research should be conducted on the correlation between the TBIL and treatment efficacy of TACE.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has been regarded as the preferred imaging modality for screening, early detection, and staging in HCC patients, as well as provides imaging biomarkers for prediction of therapeutic response and prognosis ( 13 ). Several conventional imaging features have been shown to be associated with negative response of patients with HCC: large tumor size, multiple lesions, irregular margin, faint enhancement on arterial phase, and arterial peritumoral enhancement ( 7 , 14 , 15 ). Although radiologists had attempt to standardize interpretation of liver imaging, the assessment of therapeutic response using such qualitative imaging characteristics remains subjective and variable.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified radiological patterns that correlate with response after treatment. Preoperative magnetic resonance image (MRI) features based on irregular tumor margins and abnormal AFP levels in tumors >5cm could predict non-complete response after TACE coupled to high intensity focused ultrasound in an Asiatic cohort (15). Similarly, another study set up on MRI, has indicated that large tumors and intense arterial enhancement increase probabilities of incomplete response (16).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI)-based evaluations that are noninvasive and repeatable can be used to preoperatively assess the tumor response, which take an advantage of depicting more soft-tissue characteristics than computed tomography (CT) and avoiding ionizing radiation [9] . Regarding the pretherapeutic imaging features of HCC, several scholars have reported that larger lesion diameter, irregular margin, arterial peritumoral enhancement, satellite nodule, and quantitative functional parameters of diffusion weighted imaging (DWI), intravoxel incoherent motion (IVIM), diffusion kurtosis imaging (DKI), and dynamic contrast enhanced magnetic resonance imaging (DCE-MRI), are found to be associated with therapeutic e cacy of TACE treatment [9][10][11][12][13][14][15] . Although these imaging characteristics are encouraging, they are not su cient for individual evaluations of tumor response to TACE, and the ability to predict TACE e cacy in HCC is limited when a high degree of tumor heterogeneity.…”
Section: Introductionmentioning
confidence: 99%